Estrategias de sensibilización para el desarrollo del turismo ecológico del cerro Cachari de la ciudad de Babahoyo, provincia de los Ríos - Salas Bajaña, Yadira Alejandra (2021)
This research is carried out in order to know what awareness strategies can be carried out in Cerro Cachari, a tourist destination in the City of Babahoyo.Cerro Cachari is part of one of the tourist attractions that El Canto has, it is located 9km from the town, which is a large, rocky mountain in the shape of a heart, in which you can practice various ecological tourism activities , in which the tourist is offered direct contact with nature.The research techniques of this case study are based on: documented, descriptive, diagnostic research and a technique such as the survey was used to determine the awareness strategies applicable in the development of ecological tourism in Cerro Cachari